Mechanistic Insights of the LEMD2 p.L13R Mutation and Its Role in Cardiomyopathy. Issue 2 (4th January 2023) - Chen, Ruping; Buchmann, Simone; Kroth, Amos; Arias-Loza, Anahi-Paula; Kohlhaas, Michael; Wagner, Nicole; Grüner, Gianna; Nickel, Alexander; Cirnu, Alexandra; Williams, Tatjana; Maack, Christoph; Ergün, Süleyman; et al.
Abstract : Background: Nuclear envelope proteins play an important role in the pathogenesis of hereditary cardiomyopathies. Recently, a new form of arrhythmic cardiomyopathy caused by a homozygous mutation (p.L13R) in the inner nuclear membrane protein LEMD2 was discovered. The aim was to unravel the molecular mechanisms of mutant LEMD2 in the pathogenesis of cardiomyopathy. Methods: We generated a Lemd2 p.L13R knock-in mouse model and a corresponding cell model via CRISPR/Cas9 technology and investigated the cardiac phenotype as well as cellular and subcellular mechanisms of nuclear membrane rupture and repair. Results: Knock-in mice developed a cardiomyopathy with predominantly endocardial fibrosis, left ventricular dilatation, and systolic dysfunction. Electrocardiograms displayed pronounced ventricular arrhythmias and conduction disease. A key finding of knock-in cardiomyocytes on ultrastructural level was a significant increase in nuclear membrane invaginations and decreased nuclear circularity. Furthermore, increased DNA damage and premature senescence were detected as the underlying cause of fibrotic and inflammatory remodeling. As the p.L13R mutation is located in the Lap2/Emerin/Man1 (LEM)-domain, we observed a disrupted interaction between mutant LEMD2 and BAF (barrier-to-autointegration factor), which is required to initiate the nuclear envelope rupture repair process. To mimic increased mechanical stress with subsequent nuclear envelope ruptures, we investigated mutant HeLa-cells upon electrical stimulation and increased stiffness. Here, we demonstrated impaired nuclear envelope rupture repair capacity, subsequent cytoplasmic leakage of the DNA repair factor KU80 along with increased DNA damage, and recruitment of the cGAS (cyclic GMP–AMP synthase) to the nuclear membrane and micronuclei. Conclusions: We show for the first time that the Lemd2 p.L13R mutation in mice recapitulates human dilated cardiomyopathy with fibrosis and severe ventricular arrhythmias. Impaired nuclear envelope rupture repair capacity resulted in increased DNA damage and activation of the cGAS/STING/IFN pathway, promoting premature senescence. Hence, LEMD2 is a new player inthe disease group of laminopathies.